2016
DOI: 10.1016/j.toxrep.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic inhibits stem cell differentiation by altering the interplay between the Wnt3a and Notch signaling pathways

Abstract: Millions of people are exposed to arsenic through their drinking water and food, but the mechanisms by which it impacts embryonic development are not well understood. Arsenic exposure during embryogenesis is associated with neurodevelopmental effects, reduced weight gain, and altered locomotor activity, and in vitro data indicates that arsenic exposure inhibits stem cell differentiation. This study investigated whether arsenic disrupted the Wnt3a signaling pathway, critical in the formation of myotubes and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…In the human prostate, PrSPCs give rise to basal cells, luminal PrECs, and rare neuroendocrine cells (Strand and Goldstein 2015). Because iAs alters differentiation in a variety of stemprogenitor cells (Bain et al 2016;McCoy et al 2015;Rebuzzini et al 2015;Yen et al 2010), we tested whether iAs influences this process in PrSPCs. Primary PrSPCs cultured for 7 d from diseasefree PrECs were isolated and mixed with embryonic rat urogenital sinus mesenchyme (UGM) and grafted under renal capsules of nude mice.…”
Section: Self-renewal and Differentiation Of Prspcs Treated With Or Wmentioning
confidence: 99%
“…In the human prostate, PrSPCs give rise to basal cells, luminal PrECs, and rare neuroendocrine cells (Strand and Goldstein 2015). Because iAs alters differentiation in a variety of stemprogenitor cells (Bain et al 2016;McCoy et al 2015;Rebuzzini et al 2015;Yen et al 2010), we tested whether iAs influences this process in PrSPCs. Primary PrSPCs cultured for 7 d from diseasefree PrECs were isolated and mixed with embryonic rat urogenital sinus mesenchyme (UGM) and grafted under renal capsules of nude mice.…”
Section: Self-renewal and Differentiation Of Prspcs Treated With Or Wmentioning
confidence: 99%
“…Previous studies have shown that arsenic at concentrations between 0.1 and 0.5 lM inhibit P19 embryonic stem cell differentiation into skeletal muscle and sensory neurons (Bain et al, 2016;Hong and Bain, 2012;Liu and Bain, 2014;McCoy et al, 2015). One potential mechanism for this inhibition is through changes in miRNA expression in arsenic-exposed cells, as miRNAs have been shown to play a role in arsenic toxicity and carcinogenesis (reviewed in Bustaffa et al, 2014;Paul and Giri, 2015;Ren et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…RA is derived from vitamin‐A, is a ligand for the transcription factor RA receptor, and has a critical role in development in many models, from fish to amphibians, to birds and mammals (Breitman et al, ; Baier‐Anderson et al, ; Rhinn and Dollé, ). Likewise, arsenate (As) affects cell differentiation and tissue development (McCoy et al, ; Bain et al, ), but neither RA or As affected MVP mRNA expression. The use of phorbol ester and calcium ionophore (P + A) mimics the activation of PKC and elevated intracellular calcium following cell activation and signaling (Rice and Weeks, ), and as with RA and As, this signaling has no impact on MVP mRNA expression in CCO cells under present experimental conditions.…”
Section: Discussionmentioning
confidence: 99%